2019
DOI: 10.1002/jppr.1455
|View full text |Cite
|
Sign up to set email alerts
|

The potential impact of an electronic medication management system on safety‐critical prescribing errors in an emergency department

Abstract: Background: Medication errors in hospitals are common. Although electronic medication management systems (eMMS) have the potential to reduce errors during inpatient care, little is known about their effect in emergency departments (ED). Aim: The aims of this study were to report on the types of prescribing errors in an ED prior to implementation of an eMMS, to assess the risk the errors pose to patient safety and to evaluate whether safety-critical errors were potentially preventable with a newly implemented e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Medication errors frequently occur in ED, due to its unique operating characteristics 1,2 A variety of methods have been suggested for the identification and reduction of medication errors in ED, but pharmacy has infrequently been highlighted as a solution. [3][4] However, there is emerging international evidence highlighting a growing presence of ED pharmacists where medicine-related activities have shown improved patient outcomes and decreased medication errors. [5][6][7] The Lancashire Teaching Hospitals (North West of England), comprising approximately 1000 beds over 2 sites and with over 100, 000 yearly ED attendances identified increasing pressure on the ED service especially in the early evenings (10% of all attendances occurred between 5 and 7.30pm).…”
Section: Introductionmentioning
confidence: 99%
“…Medication errors frequently occur in ED, due to its unique operating characteristics 1,2 A variety of methods have been suggested for the identification and reduction of medication errors in ED, but pharmacy has infrequently been highlighted as a solution. [3][4] However, there is emerging international evidence highlighting a growing presence of ED pharmacists where medicine-related activities have shown improved patient outcomes and decreased medication errors. [5][6][7] The Lancashire Teaching Hospitals (North West of England), comprising approximately 1000 beds over 2 sites and with over 100, 000 yearly ED attendances identified increasing pressure on the ED service especially in the early evenings (10% of all attendances occurred between 5 and 7.30pm).…”
Section: Introductionmentioning
confidence: 99%
“…Dear Editor, Raban et al 1 recently described prescribing errors made in the emergency department (ED), and showed that electronic medication management systems (eMMS) will not necessarily prevent safety-critical errors, with only two (14.3%) being considered preventable. One area contributing to prescribing errors not mentioned in that study is the issue of medication history (MH) taking.…”
mentioning
confidence: 99%